2019
DOI: 10.18551/rjoas.2019-03.16
|View full text |Cite
|
Sign up to set email alerts
|

Food Habits of the Endemic Ricefishes (Oryzias Nigrimas, Kottelat 1990) in Poso Lake, Central Sulawesi of Indonesia

Abstract: Lake Poso, one of the ancient lakes of Sulawesi, Indonesia, has several endemic fish species, including the ricefishes (Oryzias nigrimas), local name rono pahit. Populations of Poso Lake endemic species are declining, due to the introduction of alien species, lakeshore development and watershed land-use changes. One way help maintain an O. nigrimas population is through captive breeding and domestication, for which knowledge of food habits is a pre-requisite. The purpose of this research was to study the food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to Zuliani et al (2016), who stated that the RLG of carnivorous fish is 0.2-2.5 cm, omnivores was 0.6-8 cm, and herbivores was 0.8-15 cm. As for Zuliani et al (2016) and Serdiati (2019), suggested that the average intestine length of carnivorous fish was less than 1 cm, 1-3 cm for omnivores, and greater than 3 cm for herbivores. RLG is used as an indicator of the feeding habits of fish by comparing its length to the total length (Serdiati 2019).…”
Section: Relative Length Of Gut Of Oryzias Eversi From Tilanga Poolmentioning
confidence: 85%
See 3 more Smart Citations
“…According to Zuliani et al (2016), who stated that the RLG of carnivorous fish is 0.2-2.5 cm, omnivores was 0.6-8 cm, and herbivores was 0.8-15 cm. As for Zuliani et al (2016) and Serdiati (2019), suggested that the average intestine length of carnivorous fish was less than 1 cm, 1-3 cm for omnivores, and greater than 3 cm for herbivores. RLG is used as an indicator of the feeding habits of fish by comparing its length to the total length (Serdiati 2019).…”
Section: Relative Length Of Gut Of Oryzias Eversi From Tilanga Poolmentioning
confidence: 85%
“…It is measured to determine the trophic level of fish. The results from measuring the RGL of the fish are categorized as follows: <1 for fish classified as carnivorous, 1-3 for fish classified as omnivorous, and >3 for fish classified as herbivorous (Zuliani et al 2016;Serdiati 2019;Elfidasari et al 2020).…”
Section: Relative Gut Length (Rgl)mentioning
confidence: 99%
See 2 more Smart Citations
“…Mixotrophic cryptomonads, in particular, are recognized to be optimal food for planktivorous consumers [ 43 ]. Various species of the genus Oryzias (medaka) exhibit strategies of herbivores (eating phytoplankton [ 44 ]), omnivores prone to herbivory [ 45 ], or consumers of insects and microalgae [ 46 ].…”
Section: Discussionmentioning
confidence: 99%